Simulation of Reconstructive Microsurgery in Soft Embalmed Cadavers: A Teaching Module for Plastic Surgery Residents - Manikumari, Baswa; Jaggavarapu, Sasidhar Reddy; Subha, Kakumanu; Kalpana, Tumma; Muni, Roopesh Kumar Nambi; Kishve, Prajakta; Bheemesh, P. (Indian Journal of Plastic Surgery, 2022)
Background Cadaveric dissection courses—comprising flap harvesting techniques, vessel dissections, flap transfers to the defect, and microvascular anastomosis—would help residents gain confidence and master these difficult major reconstructive microsurgery procedures. Formalin embalmed bodies lack natural softness and many other features of a live body. Many soft embalming techniques have evolved to mimic live tissue and Theil technique is the most popular one among them. We explored alternate soft embalming options and started using Genelyn.Materials and Methods Over a span of 2 years (2019–2021), we have conducted three flap dissection workshops using soft-embalmed cadavers. Six soft-embalmed and two formalin-embalmed cadavers were used. Total number of participants was 80.Results Feedback of experience from the third course participants in the form of grades (1–5) for different criteria was obtained and evaluated. Confidence in the dissection of the various flaps and microsurgery is noticeable in all the participants.Conclusion Based on our experience, we propose that flap dissection and microsurgery training on soft-embalmed cadavers be included as a teaching module in the plastic surgery postgraduate curriculum.
Keywords: reconstructive microsurgery; soft embalming; cadaver training; Genelyn; resident training in plastic surgery surgical simulation